Auctions with endogenous price ceiling: Theoretical and experimental results - Robert F. Veszteg; Kenju Akai; Tatsuyoshi Saijo; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper analyzes an auction mechanism that excludes overoptimistic bidders inspired by the rules of the procurement auctions adopted by several Japanese local governments. Our theoretical and experimental results suggest that the endogenous exclusion rule reduces the probability of suffering a monetary loss induced by winning the auction, and also mitigates the problem of the winner's curse in the laboratory. However, this protection comes at the price of a lower revenue for the seller.
Keywords: C91; D44; D82; 330; common-value auctions; experiments; winner's curse